INVESTIGATION OF PARAMETRIC OSCILLATORY MOVEMENTS IN THE AUTOMOTIVE SYSTEM - Tatiana V. Avetisyan; Yakov Y. Lvovich; Andrey P. Preobrazhenskiy (International Journal of Advanced Studies)
The aim of the study is to understand the stability of automotive systems by studying parametric oscillations. The Mathieu function is used to calculate the eigenvalues of the system, which are crucial for determining the behavior of the system over time. The results of the study reveal the resonance zone of the system and provide an algorithm for calculating the eigenvalues of Mathieu functions. The results of this study can be applied to the analysis of various transport systems to assess their stability. This knowledge can be used to improve the comfort and performance of vehicles by minimizing the impact of parametric fluctuations. The study concludes that the analysis of parametric fluctuations in automotive systems can provide valuable information about the stability of the system. For a deeper analysis, the study suggests that numerical integration should be used when the modulation depth is low. This approach will allow you to get a more accurate understanding of the management of the system.